Application of the smart government concept in Indonesia - Mohammad Rizky Nur Santosa; Rahmawati Husein; Achmad Nurmandi; Helen Dian Fridayani (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
Smart government is a modern concept that prioritises efficiency, service innovation, and increased effectiveness by integrating with advances in digital technology. This research aims to determine how the smart government concept is implemented in Indonesia. This research uses descriptive qualitative research methods by utilising secondary data sources.Â  Based on the results of the study, it can be shown that the application of the smart government concept in Indonesia has been going well, as evidenced by the many innovations in government services. These innovations include applications launched by the government to improve its services to the community. The implementation of smart government in Indonesia has also seen a significant increase in government. However, it still encounters classic problems such as the slow response of government services, the lack of quality human resources, and uneven facilities and infrastructure. The implementation of smart government in Indonesia has also seen a significant increase. However, the Indonesian government still faces classic problems such as the slow response of government services, the lack of quality human resources, and uneven facilities and infrastructure.